A NiII–Bis(diphosphine)–Hydride Complex Containing Proton Relays – Structural Characterization and Electrocatalytic Studies. Issue 27 (24th June 2014) - Das, Parthapratim; Stolley, Ryan M.; van der Eide, Edwin F.; Helm, Monte L.
Abstract: The synthesis of the 1, 5‐diphenyl‐3, 7‐diisopropyl‐1, 5‐diaza‐3, 7‐diphosphacyclooctane ligand, P i Pr 2 N Ph 2, is reported. Two equivalents of the ligand react with [Ni(CH3 CN)6 ](BF4 )2 to form the bis(diphosphine)–Ni II complex [Ni(P i Pr 2 N Ph 2 )2 ](BF4 )2, which acts as a proton reduction electrocatalyst. In addition to [Ni(P i Pr 2 N Ph 2 )2 ] 2+, we report the synthesis and structural characterization of the Ni 0 complex Ni(P i Pr 2 N Ph 2 )2 and the Ni II –hydride complex [HNi(P i Pr 2 N Ph 2 )2 ]BF4 . The [HNi(P i Pr 2 N Ph 2 )2 ]BF4 complex represents the first Ni II –hydride in the [Ni(P R 2 N R′ 2 )2 ] 2+ family of compounds to be structurally characterized. In addition to the experimental data, the mechanism of electrocatalysis facilitated by [Ni(P i Pr 2 N Ph 2 )2 ] 2+ is analyzed by using linear free energy relationships recently established for the [Ni(P R 2 N R′ 2 )2 ] 2+ family. Abstract : A new member of the [Ni(P R 2 N R′ 2 )2 ] 2+ family of electrocatalysts is reported. Complex [Ni(P i Pr 2 N Ph 2 )2 ] 2+ is an electrocatalyst for proton reduction to form H2 . Additionally, we have isolated and structurally characterized the Ni II –hydride [HNi(P i Pr 2 N Ph 2 )2 ] + .